Colville of the Guards, Volume 1 (of 3) - Grant, James, 1822-1887 (Salt Lake City, UT : Project Gutenberg, 2021)
"Colville of the Guards, Volume 1 (of 3)" by James Grant is a historical novel written in the late 19th century. The story centers around the lives of two sisters, Mary and Ellinor Wellwood, who live independently at Birkwoodbrae, a small estate, and navigate their relationships with various suitors and social circles in the Scottish countryside. The narrative weaves themes of love, independence, and societal expectations against a backdrop of charming but often tumultuous rural life. At the start of the novel, the sisters engage in a poignant conversation about the sorrows of those around them, showcasing Mary's kind-heartedness as she visits an elderly neighbor in mourning. The introduction of Captain Leslie Colville, who meets Mary during her fishing excursion, hints at a budding romance amidst complex social dynamics, including his engagement to the ambitious Blanche Galloway. The sisters$1 (Blives are further complicated by the visit from Lady Dunkeld and her daughter, who aim to include them in their social gatherings, prompting Mary to reflect on the implications of their recognition compared to their independence. As the plot unfolds, underlying tensions regarding class, love interests, and the sisters' resilience in maintaining their autonomy are set against vivid descriptions of the Scottish landscape, creating a richly layered narrative. (This is an automatically generated summary.)s
Release date is 2021-10-20
Al Haines
Keywords: Soldiers -- Fiction; British -- Afghanistan -- Fiction